2019
DOI: 10.1002/acr.23748
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Engagement and Predicted Risk of Suicide Attempts in Fibromyalgia

Abstract: This is the first study to successfully apply machine learning to reliably detect suicidality in FM, identifying novel risk factors for suicidality and highlighting outpatient engagement as a protective factor against suicide. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 32 publications
(43 reference statements)
0
53
0
Order By: Relevance
“…Interestingly, among a sample of either FM patients, lower back pain patients, or healthy controls, it was found that FM patients had significantly more passive and active SI than patients with either lower back pain or no pain, after adjusting for age and gender ( 36 ). In contrast, one case-control study of almost 15,000 suicide attempters at a major US hospital as compared to general patients at the hospital found that only 1.1% of the FM sample exhibited SI ( 39 ).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Interestingly, among a sample of either FM patients, lower back pain patients, or healthy controls, it was found that FM patients had significantly more passive and active SI than patients with either lower back pain or no pain, after adjusting for age and gender ( 36 ). In contrast, one case-control study of almost 15,000 suicide attempters at a major US hospital as compared to general patients at the hospital found that only 1.1% of the FM sample exhibited SI ( 39 ).…”
Section: Resultsmentioning
confidence: 91%
“…However, this association became non-significant after controlling for age, gender, medical comorbidities, and psychiatric comorbidities ( 28 ). Interestingly, McKernan and colleagues’ ( 39 ) large scale study examining suicide attempters as compared to the general patient population at a major US hospital indicated that only 0.4% of FM patients reported suicide attempts. Similarly, another study examining almost 200,000 patients with a variety of chronic pain conditions, as well as healthy controls, found that only 31 FM patients per 100,000 person-years [i.e., the number of participants multiplied by the length of time the participants were followed for ( 46 )] exhibited SB ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On balance, some studies indicate that bootstrap optimism correction methods perform similarly to other internal validation methods (73,74), random forest models can generalize well to new data (75,76), and random forest combined with bootstrap optimism correction performs similarly to other internal validation methods and other machine learning techniques (73,77,78). There is also evidence that Walsh et al's algorithm (64) using this approach generalizes well to new samples and new suicide-related outcomes (79,80). Nonetheless, much remains unknown about how various methods perform under various conditions, so at a minimum these discrepancies indicate that it would be prudent to conduct analyses with multiple internal validation techniques.…”
Section: Internal Validationmentioning
confidence: 99%
“…The current advancements in machine learning technologies provide a new opportunity to remedy classification problems, when utilized as a supplement to recommended changes in death scene investigation practices (Stone, Holland, Bartholow, Crosby et al., ; Stone, Holland, Bartholow, Logan et al., ). Machine learning has already begun to be used to identify living cases at risk for suicide (Colic, Richardson, Reilly, & Hasey, ; Kessler et al., ; McKernan, Lenert, Crofford, & Walsh, ; Ryu, Lee, Lee, & Park, ), paving the way for the natural extension of its use for the retrospective prediction of missed suicides among the deceased (Esty et al., ).…”
Section: Introductionmentioning
confidence: 99%